Business Analysis of Pomade Rambutan Leaf Extract with Apple Aroma Anti-Gray Hair and Multipurpose as a Green Economy Alternative - Dewi Oryza Sativa, Rima; Widiatmanta, Jeka; Febrianti, Neha; Hendra Kusuma, Agung (Publisher Cv. Inara, 2025)
Blitar is the city with the largest rambutan fruit commodity. The number of plants throughout the district was recorded at approximately 283,437 trees, with a productivity level of 115 kilograms per tree. Rambutan (Nephelium lappaceum) has benefits for the health of the human body in the form of cleansing kidney function, preventing heart disease. Not only in the fruit, rambutan trees also have many benefits in every part. Tjandra's research says that rambutan leaves and skin contain compounds of tannins, polyphenols and saponins that function as a prevention of gray hair. This pomade-shaped hair styling product